Prehistoric mammals of Western Australia - McNamara, Ken (Factfocus., 2010)
"A rich accumulation of bones, many far larger than any modern-day native mammal, was excavated in 1909 from Mammoth Cave in Australia's south-west. The treasure trove was a time capsule of mammal megafauna, evidence that in prehistoric times giant animals had roamed the Australian bush."--Page 4 of cover